Self-sensing control of resonant MEMS scanner by comb-drive current feedback. (October 2021) - Brunner, David; Albert, Stephan; Hennecke, Marcus; Darrer, Franz; Schitter, Georg
Abstract: This paper proposes a novel self-sensing control concept for resonant MEMS mirrors solely based on the comb-drive current generated by the mirror movement and simple circuitry. Phase errors are immediately compensated by asynchronous switching of the driving voltage using the precise zero crossing detection by the steep current gradient. The mirror amplitude is detected based on the time difference between a comparator threshold crossing of the current signal and the zero crossing of the mirror, while it is controlled by the duty cycle of the driving voltage signal. The proper threshold setting is analyzed regarding the obtained sensitivity and uncertainty of the amplitude detection and is verified by measurements. It is found that even for symmetric out-of-plane comb-drives the scanning direction can be determined utilizing the mode coupling phenomenon of a lightweight MEMS mirror design with reinforcement structure. Experiments show that the proposed control concept results in a low optical pointing uncertainty of 0 . 52 mdeg, which allows 10 000 pixels with a precision of 10 sigma at a scanning frequency of 2 kHz. Thus a lightweight and simple design of a high performance MEMS mirror is precisely controlled in its oscillation without any additional sensors or complex circuitry.